Politisasi Agama dan Politik Kebencian pada Pemilu Presiden Indonesia 2019 - Riki Ronaldo; Darmaiza Darmaiza (Indonesian Center for Religion and Society Studies (InTReSt), 2021)
This study aims to describe the politicization of religious symbols in online media in the decide of presidential and vice presidential candidates in Indonesian election 2019. This study is a descriptive qualitative research with data collection through study document to online media news. This study found that there are two religious symbols that are massively used in determining the presidential and vice presidential candidates for the 2019 election, namely Muslim identity and religious identity. The contested 2019 presidential and vice presidential candidates are the result of the tug-of-war between religious symbols used in the early stages of the 2019 presidential election. At this stage, Muslim identity becomes an offer that is transacted in the determination of the presidential and vice presidential candidates. Likewise with ulama and a number of religious organizations. A series of religious ceremonies such as ijtihad and ijtima is also used as a legitimating medium to raise contestants for the 2019 Presidential Election. Interestingly, the results of ijtihad and ijtima are not static and standard, but dynamic and can change according to the political situation that occurs. This in turn has led to the strengthening of hate politics.